2014
DOI: 10.4067/s0717-95532014000300003
|View full text |Cite
|
Sign up to set email alerts
|

Determinantes Do Baixo Peso Ao Nascer a Partir Das Declarações De Nascidos Vivos

Abstract: RESUMOO objetivo desse estudo foi identificar a prevalência e os fatores associados ao baixo peso ao nascer (PBN) em Divinópolis, Brasil. Método: Trata-se de estudo transversal que analisou 9.987 registros de nascidos vivos hospitalares e únicos ocorridos entre 2008 e 2011. Na análise univariada utilizou-se o teste qui-quadrado e a razão de chances fixando um nível de significância de 5%. Para o controle de possíveis fatores de confusão nas associações obtidas, usou-se o modelo de regressão logística binária. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Elevated educational attainment might act as a protective factor against LBW during pregnancy, as it increases access to information, and consequently health care, and impacts family income. 6 The participation of fathers or partners in pregnancy is a subject that involves social and cultural determinants, as the experience of pregnancy is understood differently by the pregnant woman and the partner. Prenatal care contributes to each person's understanding of their roles, responsibilities, and behavioral impacts on new human beings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated educational attainment might act as a protective factor against LBW during pregnancy, as it increases access to information, and consequently health care, and impacts family income. 6 The participation of fathers or partners in pregnancy is a subject that involves social and cultural determinants, as the experience of pregnancy is understood differently by the pregnant woman and the partner. Prenatal care contributes to each person's understanding of their roles, responsibilities, and behavioral impacts on new human beings.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Thus, LBW is directly related to the access and use of healthcare services. Mesquita-Costa et al 6 concluded that fewer than seven prenatal checkups represented a 97% increase in the risk of LBW. However, both cases and controls showed an average number of prenatal checkups close to that suggested in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quanto ao peso ao nascer, os filhos das gestantes com menor escolaridade e IMCpg de baixo peso e eutrofia tiveram menores médias de peso ao nascer. Concordando com um estudo realizado em Minas Gerais, que identificou a prevalência e os fatores associados ao BPN, concluiu que quanto menor a escolaridade materna mais chances de ter crianças com baixo peso 22 . Escolaridade materna é uma variável extremamente sensível às condições socioeconômicas das famílias.…”
Section: Total N (%)unclassified